Analisis Karakter Siswa pada Pembelajaran IPAS di Sekolah Dasar Negeri 3 Kintamani - I Nyoman Sudirman; I Kadek Purnayasa (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
This study aims to analyze the character of students in learning Natural and Social Sciences (IPAS) at Elementary School 3 Kintamani. Character is an important aspect in the development of students, apart from academic knowledge. Character includes attitudes, behaviors, and values ​​that will shape individuals into good citizens. This study uses a qualitative descriptive approach to describe the condition of student character in IPAS learning. Data were collected through observation, interviews, and documentation. The results of the study indicate that character development in IPAS learning at Elementary School 3 Kintamani went well, although there were several challenges such as the lack of active student involvement and the lack of variation in learning methods. Some of the dominant character values ​​identified were responsibility, cooperation, and concern for the environment. This study recommends that teachers develop more student-centered learning methods and increase practical activities that involve exploring the surrounding environment. science lessons. It can be concluded that the largest percentage value is in the analysis indicator which has a larger number than the number of other indicators, namely so that it can be interpreted that students are able and understand the material and form student characters who are more patient, aware, careful and critical and have a great curiosity.